Training Curriculum on the Curriculum Development in Moral, Culture, and Folk Wisdom for Primary School Teachers - Sutthiporn Boonsong, Thosporn Sangsawang, Rossarin Jermtaisong, Kasina Chinsri (International Journal of Advanced Science and Technology, 2020)
The policy of Thai education has policies to provide civil society. This training curriculum tried to train elementary school teachers to enhance experience in the curriculum development on morality, culture and local wisdom. The purpose of this research was to develop training curriculum on the “Curriculum Development in Moral, Culture, and Folk Wisdom” for elementary teachers and to study the results of the training. The design was to provide research and development of which there are three integrated approaches that combine both quantitative and qualitative research methodologies. The sample used in phase 1 is for the administrators, teachers, and experts who are involved in the teaching and training of morals, culture, and folk wisdom for elementary teachers both from government and the private sector from 6 regions. The sample used in phase 2-3 is for the elementary school teachers from 6 regions. The results of the research were as follows: Phase1: results of this study on the situation and the development of training curriculum found that the administrators of the educational institution needed the training in various subjects as follows: 1) the design of the curriculum and learning resources, 2) the study of basic information 3) the structure of the curriculum 4) the purpose of the curriculum 5) the content of the curriculum 6) the methodologies for evaluation. Phase 2: The results of the training course try-out found that the experimental group was able to develop curriculum for both short-term training courses and local course curriculum. Phase 3: The performance results of the testing training curriculum and curriculum evaluation found that when being trained, the sample is more understandable and able to develop the curriculum itself. The course can be developed for both short-term training courses and school courses.